Children with recurrent pneumonia and non-cystic fibrosis bronchiectasis. Issue 1 (December 2016) - Patria, Maria; Longhi, Benedetta; Lelii, Mara; Tagliabue, Claudia; Lavelli, Marinella; Galeone, Carlotta; Principi, Nicola; Esposito, Susanna
Abstract Background Recurrent pneumonia (RP) is one of the most frequent causes of pediatric non-cystic fibrosis (CF) bronchiectasis (BE) and a consequent accelerated decline in lung function. The aim of this study was to analyse the clinical records of children with RP in attempt to identify factors that may lead to an early suspicion of non-CF BE. Methods We recorded the demographic and clinical data, and lung function test results of children without CF attending our outpatient RP clinic between January 2009 to December 2013 who had undergone chest high-resolution computed tomography ≥8 weeks after an acute pneumonia episode and ≤6 months before enrolment. Results The study involved 42 patients with RP: 21 with and 21 without non-CF BE. The most frequent underlying diseases in both groups were chronic rhinosinusitis with post-nasal drip and recurrent wheezing (81 % and 71.4 % of those with, and 85.7 % and 71.4 % of those without BE). FEV1 and FEF25–75 values were significantly lower in the children with non-CF BE than in those without (77.9 ± 17.8vs 96.8 ± 12.4, p  = 0.004; 69.3 ± 25.6vs 89.3 ± 21.9, p  = 0.048). Bronchodilator responsiveness was observed in seven children with BE (33.3 %) and two without (9.5 %;p  = 0.13). Conclusions Reduced FEV1 and FEF25–75 values seem associated with an increased risk of developing non-CF BE in children with RP. This suggests a need for further studies to confirm the diagnostic usefulness use of spirometry in such cases.